Implikasi Hukum Bagi Akta Pembiayaan Murabahah yang Tidak Sesuai dengan Prinsip Syariah - Arini Ayatik; Dyah Ochtorina Susanti; Rahmadi Indra Tektona (Jurnal Supremasi, 2022)
In Islamic banking there is financing, one of which is murabahah. All Islamic bank products must be based on sharia principles. Murabahah contract must be made with an authentic deed. The deed must be in accordance with sharia principles. This study analyzes the legal consequences for murabahah financing deeds that are not in accordance with sharia principles. The purpose of this study is to find out and analyze the legal consequences for the murabahah financing deed that is not in accordance with sharia principles. This study uses a normative juridical method, with four problem approaches, namely the statutory approach, conceptual approach, case approach, and comparative approach. The results of this study are that if the murabahah financing deed is not in accordance with sharia principles, the deed can be null and void.